Adaptive strong-field control of vibrational population in NO2+ - Voznyuk, O.; Jochim, Bethany; Zohrabi, M.; Broin, Adam; Averin, R.; Carnes, K. D.; Ben-Itzhak, I.; Wells, E. (My University, 2019)
An adaptive closed-loop system employing coincidence time-of-flight feedback is used to determine the optimal pulse shapes for manipulating the branching ratio of NO dications following double ionization by an intense laser pulse. Selection between the long-lived NO2+ and the dissociative N+ + O+ final states requires control of the vibrational population distribution in the transient NO2+. The ability to both suppress and enhance NO2+ relative to N+ + O+ is observed, with the effectiveness of shaped pulses surpassing near Fourier transform-limited pulses by about an order of magnitude in each direction, depending on the pulse energy. The control is subsequently investigated using velocity map imaging, identifying plausible dissociation pathways leading to N+ + O+. Combining the information about the N+ + O+ dissociation with a well-defined control objective supports the conclusion that the primary control mechanism involves selectively populating long-lived NO2+ vibrational states.